The Relationship between Instructional Leadership, Educational Technology Integration, and Academic Achievement of Key Stage 2 Learners - Jennylin T. Mahilum; Melissa S. Ygay (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study examined the academic achievement of key stage 2 learners and the relationship between principal instructional leadership, educational technology integration, and student performance in the district of Salvador Benedicto. Using a cross-sectional, descriptive-correlational quantitative research design, data were collected teachers through validated questionnaires measuring instructional leadership, Technological Pedagogical Content Knowledge (TPACK), and students’ achievement levels. Descriptive statistics and correlation analysis were employed to evaluate the relationships among variables. The findings revealed a very high positive correlation between principal instructional leadership and educational technology integration, indicating that strong leadership significantly supports teachers in effectively integrating technology into instruction. Conversely, the correlation between principal instructional leadership and students’ academic achievement was weak and statistically insignificant, suggesting that leadership alone does not directly ensure higher student performance. Analysis of student achievement showed that the majority of Grade 4-6 students attained satisfactory to very satisfactory levels, with only a small proportion achieving outstanding performance. These findings highlight the critical role of instructional leadership in facilitating technology use among teachers while emphasizing the need for additional strategies, interventions, and professional development to enhance students’ academic outcomes. The Instructional Leadership and Technology Integration Enhancement Program (ILTEP) for key stage 2 learners was created as a result of the study.